Care in subsequent pregnancies following stillbirth: an international survey of parents - Wojcieszek, A.M. (2016)
OBJECTIVE: To assess the frequency of additional care, and parents' perceptions of quality, respectful care, in pregnancies subsequent to stillbirth. DESIGN: Multi-language web-based survey. SETTING: International. POPULATION: A total of 2716 parents, from 40 high- and middle-income countries. METHODS: Data were obtained from a broader survey of parents' experiences following stillbirth. Data were analysed using descriptive statistics and stratified by geographic region. Subgroup analyses explored variation in additional care by gestational age at index stillbirth. MAIN OUTCOME MEASURES: Frequency of additional care, and perceptions of quality, respectful care. RESULTS: The majority (66%) of parents conceived their subsequent pregnancy within 1 year of stillbirth. Additional antenatal care visits and ultrasound scans were provided for 67% and 70% of all parents, respectively, although there was wide variation across geographic regions. Care addressing psychosocial needs was less frequently provided, such as additional visits to a bereavement counsellor (10%) and access to named care provider's phone number (27%). Compared with parents whose stillbirth occurred at ≤ 29 weeks of gestation, parents whose stillbirth occurred at ≥ 30 weeks of gestation were more likely to receive various forms of additional care, particularly the option for early delivery after 37 weeks. Around half (47-63%) of all parents felt that elements of quality, respectful care were consistently applied, such as spending enough time with parents and involving parents in decision-making. CONCLUSIONS: Greater attention is required to providing thoughtful, empathic and collaborative care in all pregnancies following stillbirth. Specific education and training for health professionals is needed.